Disordered CYP11B2 Expression in Primary Aldosteronism - Gomez-Sanchez, Celso E.; Kuppusamy, Maniselvan; Reincke, Martin; Williams, Tracy Ann (Hormone and Metabolic Research, 2017)
Primary aldosteronism is the most common type of secondary hypertension affecting 6–10% of patients with primary hypertension. PA is mainly caused by unilateral hyperaldosteronism due to an aldosterone-producing adenoma, unilateral hyperplasia with or without micronodules or bilateral zona glomerulosa hyperplasias with or without macro or micronodules. The development of antibodies against the terminal enzyme of aldosterone biosynthesis (CYP11B2) has permitted the further characterization of normal adrenals and resected adrenals from patients with primary aldosteronism. Normal adrenals exhibit two different patterns of cellular expression of CYP11B2: young individuals display a relatively uniform expression of the enzyme throughout the zona glomerulosa while the adrenals of older individuals have dispersed CYP11B2-expressing cells but have more groups of cells called aldosterone-producing cell clusters (APCC). APAs exhibit different patterns of CYP11B2 staining that vary from uniform to homogeneous. There are also a proportion of cells within the APA that co-express different enzymes that are not normally co-expressed in normal individuals. Approximately 30% of patients with unilateral hyperaldosteronism do not have an APA, but either have an increased number of CYP11B2 expressing micronodules or hyperplasia of the zona glomerulosa. In summary, the studies reported in this review are shedding new light on the pathophysiology of primary aldosteronism. The wide variation in histopathological features of the adenomas and concurrent presence of APCCs raises the possibility that most cases of unilateral production of aldosterone actually might represent bilateral asymmetric hyperplasia with nodules frequently due to the development of somatic aldosterone-driving mutations.
Keywords: aldosteronism; aldosterone synthase; promary aldosteronism; immunochemistry